2016
DOI: 10.1111/fwb.12824
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and spatial characterisation of an unknown fauna using DNA sequencing – an example with Himalayan Hydropsychidae (Insecta: Trichoptera)

Abstract: Summary Ecological studies of freshwater biota in understudied regions are often obstructed by poor taxonomic knowledge. We posit that molecular tools can help alleviate this issue and present an example where we combined molecular tools, environmental data and ecological statistics to investigate the distribution and community ecology of an unknown fauna of hydropsychid caddisflies along altitudinal gradients in four Himalayan river systems of Central and Eastern Nepal. A total of 484 larval specimens from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
(118 reference statements)
2
17
0
Order By: Relevance
“…Our findings, along with those of Hoppeler et al . () support the assertion that highland headwaters can support considerable beta diversity (Finn et al ., ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our findings, along with those of Hoppeler et al . () support the assertion that highland headwaters can support considerable beta diversity (Finn et al ., ).…”
Section: Discussionmentioning
confidence: 89%
“…Hoppeler et al . () found extremely high turnover and narrow elevational ranges in genetically identified operational taxonomic units of hydropsychid caddisflies in these streams. Our findings, along with those of Hoppeler et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using these tools is particularly beneficial for studying evolutionary or ecological patterns in taxonomically understudied areas [128, 134]. When integrated into larger databases these data on evolutionary lineages and species can be further used for large-scale evolutionary or phylogenetic studies [66].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the COI locus has been demonstrated to be an effective method for resolving population-level and specieslevel differences for Collembola, as well as identifying cryptic species (e.g., Hogg & Hebert, 2004;Porco, Bedos, & Deharveng, 2010;Raschmanová et al, 2016). Previous studies using multiple markers, including COI, have shown that COI is likely to be representative of overall genomic differences and is an appropriate measure of genetic differentiation between populations (e.g., Hoppeler et al, 2016;Stevens & Hogg, 2003;Saltzwedel, Scheu, & Schaefer, 2016). Here, we determine genetic variability, using COI, for Collembola across large-scale Namib Desert soil transects, and assess the spatial distribution of COI haplotypes and putative species-level groupings as an indication of population connectivity and dispersal.…”
mentioning
confidence: 99%